2021
DOI: 10.1007/s00216-021-03306-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen monoxide as dopant for enhanced selectivity of isomeric monoterpenes in drift tube ion mobility spectrometry with 3H ionization

Abstract: The ion mobility spectra of the isomeric monoterpenes α-pinene, β-pinene, myrcene, and limonene in drift tube ion mobility spectrometry (IMS) with 3H radioactive ionization are highly similar and difficult to distinguish. The aim of this work was to enhance the selectivity of IMS by the addition of nitrogen monoxide (NO) as dopant and to investigate the underlying changes in ion formation responsible for the modified ion signals observed in the ion mobility spectra. Even though 3H-based-IMS systems have been u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In an APCI source with (H 2 O) n H + as the RI, the ionization mechanism is based on proton transfer and it is expected that [M + H] + is formed as the major product ion for the phenyl butanone isomers. Recently, Weller et al 48 studied ionization of monoterpenes in the presence of NO + and reported that NO + can ionize these compounds via hydride abstraction, charge transfer, and fragmentation. In our study, the mass spectra of the phenyl butanones in vapor with M + , [M – H] + , and many fragment ions also indicate the presence of NO + as one of the main RIs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an APCI source with (H 2 O) n H + as the RI, the ionization mechanism is based on proton transfer and it is expected that [M + H] + is formed as the major product ion for the phenyl butanone isomers. Recently, Weller et al 48 studied ionization of monoterpenes in the presence of NO + and reported that NO + can ionize these compounds via hydride abstraction, charge transfer, and fragmentation. In our study, the mass spectra of the phenyl butanones in vapor with M + , [M – H] + , and many fragment ions also indicate the presence of NO + as one of the main RIs.…”
Section: Resultsmentioning
confidence: 99%
“…In an APCI source with (H 2 O) n H + as the RI, the ionization mechanism is based on proton transfer and it is expected that [M + H] + is formed as the major product ion for the phenyl butanone isomers. Recently, Weller et al 48 studied ionization of also be due to diffusion of the neutral molecules into the discharge and reactions with electrons, N 2 + , and O 2 + , comparison of the thermodynamic data and mass spectra suggested that the probability of this pathway is low. The multichannel ionization mechanism of the phenyl butanones with several product ions also leads to complicated total ion mobility spectra with different patterns in different solvents (Figure S13).…”
Section: Methodsmentioning
confidence: 99%
“…To overcome these issues, a range of modifier or dopant gases are introduced into the CD ion source to convert the standard RIs to dopant RIs and thus change the ionization mechanism. Such dopants are used to improve the sensitivity and selectivity of the ionization process, modify the nature of the analyte ions (the ion mobilities of the analyte ions) to reduce the IMS peak overlapping, and even to achieve conformer and chiral separation. …”
Section: Introductionmentioning
confidence: 99%
“…In the positive polarity, the most common dopant gases are NH 3 , NO, and NO 2 , which produce NH 4 + ·(H 2 O) m and NO + ·(H 2 O) n RIs. ,, As NH 3 has higher gas phase basicity than H 2 O, ionization of analytes by NH 4 + ·(H 2 O) m is more selective than that by H 3 O + ·(H 2 O) m so that only compounds with higher basicity than NH 3 are protonated . However, compounds with basicity lower than NH 3 can also be ionized via ammonium attachment, [M + NH 4 ] + , leading to IM peak shift compared to ionization by H 3 O + RIs .…”
Section: Introductionmentioning
confidence: 99%
“…One potential challenge of IMS analysis is that spectra may contain interference due to widespread ionization, which results in low selectivity. The addition of suitable dopant substances, however, has been shown to overcome these limitations [ 53 , 54 ]. A nonlinear concentration range was previously described for IMS, requiring the careful monitoring of sample concentration to avoid sample saturation.…”
Section: Introductionmentioning
confidence: 99%